Strategies Used to Enhance Parent Involvement on Performance of Early Childhood Education in Kisii, Nyamira and Homabay Counties, Kenya - Okendo, Ogoti Evans (International Journal of Educational Technology and Learning, 2018)
The study sought to establish investigate the strategies that enhance parent involvement on performance of Early Childhood Education in Kisii, Nyamira and Homabay counties. The study was based on Epstein’s theory of overlapping spheres of influence. This study employed a convergent parallel design. Data was collected from 223 respondents who included parents, head teachers, ECD teachers and programme officers from the three counties. The respondents were sampled using probability and non- probability sampling procedures. Questionnaires, interview guide and observation schedules were used to collect primary data. A pilot test was conducted in five schools in Kisii South Sub-County to assess validity of the research instruments whereas split half method used to ascertain the reliability of questionnaire, dependability and credibility determined the reliability of interview guide. Quantitative data was analyzed using both descriptive and inferential statistics while qualitative data was analyzed thematically. From the findings, collaboration with community strategy contributed the highest percentage to the performance of Early Childhood Education followed by communication from school and to school, decision-making and volunteering. The study recommended that is necessary that parents track their children’s academic progress by consulting with the teachers and checking the report books.